(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This work is aimed at studying the mixing time and pressing speed of composite pasta made from local soft wheat flour, soybeans, and buckwheat. During the research, the influence of various mixing and pressing conditions on the physicochemical properties of the dough is analyzed. Based on the obtained results, optimal parameters are determined. This makes it possible to improve product quality, effectively organize the production process, and ensure energy efficiency. It also serves to determine the role of innovative technologies in pasta production.